The Chapel Royal, the First Edwardian Prayer Book, and Elizabeth's Settlement of Religion, 1559 - Bowers, Roger (The historical journal, 2000)
Already at the beginning of her reign Elizabeth I was resolved to effect at the earliest opportunity both the restoration of the Royal Supremacy and the replacement of the Latin liturgy by an existing Edwardian Prayer Book. Constrained by Marian legislation which she was firmly minded not to break, the queen signalled her intentions by conspicuous adoption in her Chapel Royal of such few and minor manifestations of Protestant liturgy and practice as fortuitously were still legitimate, amplified by certain early Edwardian practices (1547–9) originally introduced not by statute but by proclamation or injunction and therefore never formally de-legitimated by statutory repeal. That her initial intention was restoration of the Prayer Book of 1549 is indicated by the identity of certain texts set to music early in 1559 by her Chapel Royal composers, and by the response of Edmund Guest to a contemporary request that he undertake a revision of parts of the 1549 Book. Arising from her own personal convictions, Elizabeth's policy was not without merits; however, political pragmatism and ecclesiastical realities coerced her into agreeing instead to the restoration of the Book of 1552. She exacted a number of concessions to her own conservatism ; first discernible in the instructions given to Guest, these achieved their realization through the rubrics of the 1559 Prayer Book and certain of the 1559 Injunctions.